PENGGUNAAN TIPE KLAUSA PADA HARIAN BALI POST - Ni Luh Komang Candrawati (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
This paper aims at describing the markers and its appearance in various types of construction on the articles structure in the Bali Post Newspaper and its role in sentence structure. The method used in this paper is observation method. In data collection, the observation method is applied with note-taking techniques and classifying the types of markers based on the sentence structure in some articles of Bali Post Newspaper. The data analysis method used is the distributional method (Sudaryantto, 1988) with the direct element sharing technique, as well as the permutation and deletion techniques as advanced techniques. Furthermore, this paper uses the conceptual basis proposed by Quirk et al. (1985), Hoed (1978), Fokker (1980), Alwi et al. (1998), and Kaswanti Purwo (1984). The results of this study indicate that the clause structure in the news or articles in the Bali Post Newsaper is in the form of an synthetic structure which is realized in participial construction, block language, and clause that. In the type of the block language in the title of the newspaper / news, the presence of a conjunction marker is semantically mandatory. The clause structure that is a loose type and a strict type in the relationship between the predicate and the clause that follows it.